(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, based on the state policy on youth in the Republic of Uzbekistan and five initiative projects, information is provided on educating young people as spiritually mature people, helping them to grow up in a healthy environment, and to help them become specialists in their profession in the future in this current time. Moreover, detailed information will be given about the education and upbringing of the child in the family circle, together with the measures taken in the formation of the spirituality of our youth together with the neighborhood and teachers. Educating young people with loyalty to the motherland, with the spirit of love for the nation and its people, and in raising them to be spiritually mature people, is first and foremost, the role of the family and educational institutions, as well as the neighborhood, is incomparable. We reflect on the opportunities and conditions created for our youth nowadays.